Perancangan Buku Fotografi Fashion Batik Jawa Timur Sebagai Upaya Meningkatkan Citra Budaya - Theofilus Christ Marvellianto; Sarjono Sarjono; Ahmad Zakiy Ramadhan (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
This book also explains about the origin of batik patterns from its region. Batik, which is the authentic traditional clothing of East Java, is losing its existence. Less knowledge about East Java batik makes it more outdated particularly from younger generation. This fashion photography book is expected to be a guide and solution for younger generation appreciating and perceiving fashion style, especially East Java batik. This fashion photography book is made to actively exhibit various kind of East Java batik that making an actual progress day by day. The information about the pattern of the batik is shown in this book, so that the public become more familiar with the origin of East Java batik. Perhaps, this book can increase the public interest to wear the origin batik of East Java.There are two sources of the data taken for this fashion photography book, which are primary and secondary data. The data collected by interviewing several interviewees, observing several books, and using the modification framework plan by Sanyoto. The result of this book design can be used as the media of fashion photography book for public to know more about East Java batik. This book can be used to educate and increase the public awareness and interest to wear the traditional attire specifically, East Java batik.